Cyber Security and Educational Institution in Nigeria: Benefits and Challlenges (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study discussed the import of cyber security in the educational institution in Nigeria. The paper also looked at the challenges militating against development of cyber security in the institutions. The paper depend on secondary data. The secondary data were collected from online and print resources. The paper identified protection of students and staff data, stable academic programme, stable school administration, stable virtual learning programme and confidence in school integrity as the benefits of cyber security development in the Nigeria’ educational institutions. The paper also identifies inadequate funding, inadequate infrastructure, technological advancement, poor training and shortage of cyber security professionals as challenges militating against cyber security development in educational institutions in Nigeria. Based on the findings, the study recommends the following: the government should direct all educational institutions to embark on cyber security programme that will ensure safety of students and staff data from their part. The federal and state government should provide special funding for the implementation of cyber security programme in all public institutions across Nigeria. The government should provide cyber infrastructure facilities across the states and local government to support effective implementation of cyber security programme.